An Epistemology of Fraudulent Financial Reporting: a Business Model Canvas Adoption - Anindyo Widhoyoko, Samuel; ., Sasmoko; Peranginangin, Ezra; Gultom, Jonathan; Handayani, Sri (International Journal of Engineering and Technology, 2018)
As an emerging trends of business, new development of epistemology is necessary. In the field of forensic accounting and fraud examination, numerous model on how fraud could happen have been evolving innovatively. On the other hand, fraudulent financial reporting scheme has never been explained in an epistemological manner. As business process is growing more sophisticated and complicated these days, an epistemology development must be done grounded on a representative business framework in which, this research employs business model canvas (BMC) by Alexander Osterwalder due to its adaptability and flexibility. This research interprets the elements contained in BMC in the context of fraudulent reporting in stock market through sequential explanation presented in the model.
Keywords: business Model Canvas; Fraudulent Financial Reporting; Stock Market Fraud.